Associations between dairy consumption, physical activity, and blood pressure in Chinese young women - Lu, Yining; Wiltshire, Huw D.; Baker, Julien S.; Wang, Qiaojun; Ying, Shanshan (Frontiers in Nutrition, 2023)
The prevalence of hypertension (HTN) has been increasing in young adults. A healthy dietary pattern and increasing physical activity (PA) are commonly recommended as the lifestyle modifications needed to manage blood pressure (BP). However, little is known about the relationship between dairy intake, PA, and BP in Chinese young women. The aim of this study was to examine whether BP was associated with dairy intake, moderate-to-vigorous intensity physical activity (MVPA) and total physical activity (TPA) in a sample of Chinese young women. A total of 122 women (20.4 ± 1.4) who had complete data sets from the Physical Fitness in Campus (PFIC) study were included in this cross-sectional analysis. Data related to dairy intake and PA was collected using a food frequency questionnaire and an accelerometer. BP was measured following standardized procedures. The association between BP with dairy intake and PA was examined using linear regression models. After controlling for potential covariables, we observed a significant and independent relationship only between systolic BP with dairy intake (b = -0.275, p < 0.001), MVPA (b = -0.167, p = 0.027), and TPA (b = -0.233, p = 0.002). Furthermore, we found a decrease of 5.82 ± 2.94, 1.13 ± 1.01, and 1.10 ± 0.60 mm Hg in systolic BP for daily additional servings of dairy, 10 minutes of MVPA, and 100 counts per minute of TPA, respectively. Our results support the protective effect of increasing dairy consumption and PA in Chinese young women on BP. Our findings also indicate that a combined strategy appeared to be more effective than diet or PA alone in lowering systolic BP.